The effects of three techniques that change the wetting patterns over subsurface drip-irrigated potatoes - Elnesr, Mohammad N.; Alazba, Abdurrahman A. (Spanish Journal of Agricultural Research, 2015)
Wetting pattern enhancement is one of the goals of irrigation designers and researchers. In this study, we addressed three techniques (dual-lateral drip, intermittent flow and physical barrier methods) that change the wetting pattern of subsurface drip irrigation. To study their effect on the yield and water-use efficiency (WUE) of potatoes, field experiments were conducted for four seasons, during which the soil-water balance was continuously monitored using a set of capacitance probes. The results of the soil water patterns showed that both the dual-lateral and intermittent techniques increased lateral water movement and eliminated deep percolation, whereas the physical barrier had a limited effect on the top soil layer. The crop results indicated that the yield and WUE increased significantly in response to the application of the dual-lateral drip (up to 30%); the intermittent application also positively affected the yield (~10%) and the WUE (~14%), but these effects were not statistically significant according to the statistical model. The physical barrier showed a non-significant negative effect on the yield and WUE. These findings suggest the following recommended practices: the use of dual-lateral drip technique due to its beneficial results and its potential for increasing yields and reducing water consumption; the application of intermittent flow with more than three surges; and restricting the use of physical barriers to soils with high permeability.